Microwave-Assisted Deep Eutectic Solvent Extraction of Lipids from Ulva sp.: Optimization and Fatty Acid Profiling - Rizkiana, Meta Fitri; Lestari, Afrila Tutut Dwijati; Sholeha, Irdatus; Palupi, Bekti; Putri, Ditta Kharisma Yolanda; Rahmawati, Istiqomah; Amini, Helda Wika; Fachri, Boy Arief (Jurnal Pijar Mipa, 2025)
Ulva sp. is a green alga commonly found in Indonesian waters. It contains approximately 60% carbohydrates, 10–47% protein, and 1–3% lipids. This study aimed to determine the optimum conditions for lipid extraction from Ulva sp. A pre-treatment step was carried out by adding a Deep Eutectic Solvent (DES) and distilled water. The DES used was a mixture of zinc chloride and urea in a 1:2 molar ratio. The sample was then mixed with a chloroform-methanol solvent (2:1 v/v) and subjected to Microwave-Assisted Extraction (MAE). The variables investigated in this study included microwave power (150, 300, and 450 W), extraction time (10, 15, and 20 min), and solvent volume (45, 60, and 75 mL). The organic phase obtained from the extraction process was separated and evaporated to determine the lipid yield. The highest yield, 15.8%, was achieved under conditions of 20 min extraction time, 75 mL solvent volume, and 300 W of power. GC-MS analysis of the highest-yield sample revealed the presence of fatty acids including palmitic acid, oleic acid, and palmitoleic acid. This optimized method supports future applications in biodiesel production and green extraction processes for algae-based bioresources.